Chemistry in the marine environment - Harrison, Roy M., 1948-; Hester, R. E. (Issues in environmental science and technology, 2000)
The oceans cover more than 70% of the earth's surface to an average depth of almost 4000 metres. It is therefore not surprising that exchanges that occur between ocean and atmosphere exert major influences on the global climate. In addition, there is great variety within the expanses of the ocean, including large temperature differences, and enormous biodiversity brought about by the great chemical diversity within the marine environment. Written by international experts in the field, Chemistry in the Marine Environment offers a multidisciplinary and authoritative review of this important topic. Included is a review of the opportunities and challenges in developing new pharmaceuticals from the sea and an examination of contamination and pollution in the marine environment, which is a cause of great concern world-wide. The international perspective of this book will engage the interest and attention of a wide readership, from chemical oceanographers to policymakers, from students in environmental science to those in oceanography programmes.